The decrease in population bone lead levels in Canada between 1993 and 2010 as assessed by in vivo XRF. (28th December 2017) - McNeill, F E; Fisher, M; Chettle, D R; Inskip, M; Healey, N; Bray, R; Webber, C E; Manton, W I; Marro, L; Arbuckle, T E
Abstract: Objective and Approach : A study, conducted in Toronto, Canada, between 2009 and 2011, measured the bone lead concentrations of volunteers aged 1–82 years using in vivo x-ray fluorescence (XRF) technology. Main results : Bone lead levels were lower compared to Ontario in vivo XRF studies from the early 1990s. In adults, the slope of tibia lead content versus age was reduced by 36–56%, i.e. bone lead levels for a given age group were approximately half compared to the same age group 17 years prior. Further, bone lead levels of individuals fell over that time period. In 2010, an average person aged 57 years had a bone lead level approximately 1/3 less than their bone lead level age 40 years in 1993. Using this data, the half-lives of lead in the tibia were estimated as 7–26 years. Tibia lead levels were found to be low in children. The reduction in bone tibia content in children was not significant ( p   =  0.07), but using data from additional north eastern US studies, there is evidence that childhood tibia stores are lower than in the 1990s. Significance : In vivo XRF analysis shows that there has been a reduction in the level of lead in bone in Canada over the last two decades. Public health measures have been very successful in reducing ongoing exposure to lead and in reducing bone lead stores.